PARADIGMA KONTEMPORER EKONOMI ISLAM (Muh. Abdul Mannan versus Syed Nawab Haedir Naqvi) - Yusuf, Asdar (Hunafa: Jurnal Studia Islamika, 2014)
The Islamic economic paradigm calls more  the attention when the contemporary world encourages the emergence of various kinds of thoughts, ideas, concepts. universality, productivity, reality, creativity, and even  morality. Nevertheless, some of the basic assumptions of the core conception of the paradigm begins to be questioned.  The problems are no more related  to the perception of the mind, the ideas and the final product, but has covered the basic assumption  about human nature, motivation, and effort, which became the basis of the economic assumption in which the agents  work. This paper presents the overview of  Muh. Abdul Mannan versus Syed Nawab Haedir Naqvi  in three aspects of the study: the interpretation of some economic terms and concepts in the Qur'an and Sunnah, the approach employed in building  theory and  Islamic economic system as well as  their views on the interpretation of the Islamic economic system.Kata kunci: Ekonomi Islam, Muh. Abdul Mannan, Nawab Haedir Naqvi